Endogenous knowledge and human disturbance impact on abundance of two underutilized wild edible tree in southern Benin - Vitoule, E.T; Houéhanou, T.; KASSA, DAHOGA BARTHÉLÉMY; ASSOGBADJO, ACHILLE EPHREM; Glèlè kakaï, Romain; Djego, Julien; SINSIN, Brice (My University, 2014)
This study assessed endogenous knowledge and impact of human disturbance on the abundance of two underutilized wild fruit tree species: Drypetes floribunda (Mu¨ll. Arg.) Hutch. (Euphorbiaceae) and Mimusops andongensis Hiern. (Sapotaceae) in the Lama Forest Reserve (LFR) in southern Benin. A survey was conducted with 145 randomly selected people amongst the surrounding communities of LFR in order to assess the endogenous knowledge of the species. One hundred square plots were established in the forest for characterizing species abundance in different habitats according to human disturbance degree. Results indicated that this species has multiple uses and either local knowledge on their uses or their organ plant uses depend on social factors. A densities assessment suggests a negative effect of human disturbance on the abundance of both species. Results support the need to envisage conservation and sustainable use strategies as perspective policies.
Keywords: Drypetes floribunda; Mimusops andongensis; use; abundance; Lama Forest Reserve; Benin